Effect of a digital guide on the positional accuracy of intermaxillary fixation screw implantation in orthognathic surgery. Issue 7 (July 2022) - Cui, Ming-xue; Xiao, Le-cun; Yue, Jin; Xue, Ling-fa; Xiao, Wen-lin
Summary: Background: Intermaxillary fixation screw (IMFS) implantation is a common procedure in orthognathic surgery (OGS) performed to the temporary maxillary-mandibular fixation and stable bite relationships. The study aims to assess the accuracy of IMFS implantation with a digital guide to reduce the occurrence of root damage. Methods: This prospective study involved 40 patients undergoing OGS at the Affiliated Hospital of Qingdao University from August 2017 to May 2021. The patients were randomly divided into two groups according to whether the IMFS implantation was with or without digital guide (20 patients in the experimental group and 20 controls). The digital guides used in the experimental group were designed according to a virtual implantation plan and printed using stereolithography. In the control group, IMFSs were directly implanted by a surgeon based on clinical experience. Postoperatively, cone-beam computed tomography was performed to compare root proximity of IMFSs between the two groups and verify the accuracy of IMFS placement. Results: In the experimental group, there was no case of root damage, the incidence of the periodontal ligament (PDL) injured was 22.1%, and 77.9% IMFSs were placed without contacting adjacent anatomic structures. In the control group, the incidence of root damage had been up to 20.8%, 31.7% IMFSs injured the PDL, and only 47.5% IMFSs were placed between the roots ( P  < 0.001). Conclusion: IMFSs can be placed more accurately with surgical guides, reducing the incidence of root and PDL damages.